2012
DOI: 10.1074/jbc.r111.318675
|View full text |Cite
|
Sign up to set email alerts
|

Pleckstrin Homology Domain Leucine-rich Repeat Protein Phosphatase (PHLPP): A New Player in Cell Signaling

Abstract: Precise balance between phosphorylation, catalyzed by protein kinases, and dephosphorylation, catalyzed by protein phosphatases, is essential for cellular homeostasis. Deregulation of this balance leads to pathophysiological states that drive diseases such as cancer, heart disease, and diabetes. The recent discovery of the PHLPP (pleckstrin homology domain leucinerich repeat protein phosphatase) family of Ser/Thr phosphatases adds a new player to the cast of phosphate-controlling enzymes in cell signaling. PHL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 45 publications
0
65
0
Order By: Relevance
“…PHLPP1 is recognized as a tumor suppressor with a prominent role in suppressing oncogenic signaling pathways, including the AKT pathway (for review, see refs. 22,23). Interestingly, another member of this family of phosphatases, PHLPP2, is a potential target of miR15a, which we found to be upregulated in deep sequencing and Northern blotting in all prostate carcinoma samples.…”
Section: Sec23a Is a Target For Mir-200bmentioning
confidence: 90%
See 2 more Smart Citations
“…PHLPP1 is recognized as a tumor suppressor with a prominent role in suppressing oncogenic signaling pathways, including the AKT pathway (for review, see refs. 22,23). Interestingly, another member of this family of phosphatases, PHLPP2, is a potential target of miR15a, which we found to be upregulated in deep sequencing and Northern blotting in all prostate carcinoma samples.…”
Section: Sec23a Is a Target For Mir-200bmentioning
confidence: 90%
“…A downregulation of PHLPP1 or PHLPP2 could be detected in 11% of primary prostate carcinoma and in 37% of metastases (23,36). Recently, it has been reported that both PHLPP1 and PHLPP2 are deleted or downregulated in combination with highly metastatic prostate carcinoma (22) or glioblastoma (37). PHLPPs belong to a family of phosphatases that regulate protein kinases A, B (known as Akt), and C and ribosomal protein S6 kinase (RPS6K) negatively (23,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PHLPP2 is a member of this family. 2,3 To date four PHLPP substrates, Akt, PKC, Mst1 and S6K1, have been identified, all kinases involved in cell survival or apoptosis. [4][5][6][7] Dephosphorylation inactivates Akt, S6K1 and PKC, and subsequently cell survival signaling, whereas dephosphorylation of Mst1 activates its apoptotic function.…”
mentioning
confidence: 99%
“…PHLPP directly dephosphorylates AKT at its hydrophobic motif (Ser473). AKT is a crucial player to execute intracellular responses post IRS-1 (insulin receptor substrate-1) phosphorylation (Machado-Neto et al 2011, Warfel & Newton 2012.…”
Section: Introductionmentioning
confidence: 99%